Reactive nitrogen and oxygen intermediates in patients with cutaneous leishmaniasis - Erel, O; Kocyigit, A; Bulut, V; Gurel, MS (Fundaco Oswaldo Cruz, 1999)
[Abstract Not Available]
Keywords: nitric oxide; superoxide dismutase; catalase; glutathione peroxidase; leishmaniasis